Analisis Kemampuan Metakognisi Siswa dalam Pemecahan Masalah Matematika - Iryani Dinar Dinar; Yanti Mulyanti; Hamidah Suryani Lukman (Prodi Pendidikan Matematika, FKIP, Universitas Balikpapan, 2022)
This study aims to describe the metacognitive ability and level of metacognition of class XII SMK students in the process of solving mathematical problems. Metacognition ability in solving the problem in question is the awareness of thinking by involving the planning process, monitoring/monitoring process and evaluation process at Polya's steps, namely the stages of understanding the problem, planning, completing and re-examination. This study uses a descriptive approach. This research was conducted at SMK Negeri 3 Sukabumi with subjects from class XII Catering 4 consisting of three students as representatives of the high, medium and low problem solving groups. Data collection using test and interview methods. The test instruments used are three explanations of problem solving material limits on algebraic functions. The data analysis process in this study includes data reduction, data presentation and conclusion drawing. Based on the results of data analysis, it was found that the dominant metacognitive ability possessed by high subjects was the process of planning, monitoring and evaluation at the stage of understanding and planning for completion. Meanwhile, the metacognitive abilities of the moderate and low groups were dominantly not seen as complete and fulfilled in every step of problem solving. The metacognition level of the high group students was at the level of strategic use, the middle group students was at the level of aware use and the low group students was at the level of tacit use.